Dehydrogenation and oxidative dehydrogenation of alcohols on silica supported chromium catalysts - Parentis, Monica Liliana (2002)
The catalytic activity of Cr/SiO2 (0.43 to 2.8% chromium by weight), prepared by the ion exchange method, for the dehydrogenation (573 K to 673 K)and oxidative dehydrogenation (503 K to 558 K) of alcohols has been investigated. The results obtained are consistent with the hypothesis that Lewis pyridine centers of chromium are the active sites for alcohol dehydrogenation. At 593 K the selectivity to aldehyde is 70% while selectivity to acetone is 62%, for pure dehydrogenation. The dehydrogenation rate of secondary alcohol is one order of magnitude higher than that observed for primary ones. The catalytic activity for oxidehydrogenation is 12 times higher than for pure dehydrogenation and the reaction rate of primary alcohols are higher than for secondary ones. When the ratio of oxigen to alcohol partial presure is 1:2 or above, the selectivity to aldehydes reach values of 97%, 89% and 80%, for ethanol, propanol and butanol, respectively, while the selectivity for secondary alcohols remains as in dehydrogenation (60%).